Sacred Conjugality and the Post-Nikah Metamorphosis: An Islamic Exegesis on Responsibility, Emotional Elevation, and Divine Purpose - Rafia Mushtaq; Azra Mushtaq (CV. Radja Publika, 2025)
This paper expounds upon the post-nikah transformation of human existence through the lens of Islamic theology, emotional psychology, and ethical responsibility. Anchored in Qur’anic injunctions and Prophetic traditions, the discourse delineates marriage not as a mere social construct but as a metaphysical alliance imbued with divine intentionality and existential recalibration. Marriage, as articulated within the Islamic framework, is portrayed as a covenant that transcends legal formalism and enters the domain of spiritual actualization and moral evolution. The study examines how the advent of conjugal life catalyzes a metamorphosis—from individualistic autonomy to symbiotic stewardship—thus manifesting a higher order of accountability, emotional resilience, and sacred companionship. By drawing upon classical Hadith literature and contemporary relational paradigms, the paper advocates for the sacralization of marital roles and responsibilities as intrinsic to human purpose. Recommendations are offered both to the unmarried—urging a reorientation toward divine trust and simplicity—and to married individuals—encouraging a reframing of domestic life through the optics of mutual mercy, forgiveness, and transcendent growth. Ultimately, the treatise asserts that life after nikah is not a diminution of freedom but a sanctified elevation of the self toward a more meaningful and God-conscious existence.